A fluorine-aluminum co-doped lithium cobalt oxide positive electrode material and preparation method thereof

Through the preparation method of lithium cobalt oxide co-doped lithium cobalt oxide positive electrode material, an aluminum fluoride coating layer is formed, which solves the problem of poor cycling performance of lithium cobalt oxide at high voltage, and significantly improves the cycling stability and capacity retention rate of the battery .

CN114695862BActive Publication Date: 2025-01-10GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202210298899.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-25
Publication Date
2025-01-10
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

The existing lithium cobalt oxide positive electrode materials have poor cycling performance at high voltages, resulting in collapse of the material structure and cobalt dissolution, reducing the cycling stability of the battery.

Method used

The preparation method of lithium cobalt oxide co-doped lithium cobalt oxide positive electrode material is adopted. The mixture precipitation of cobalt salt solution, aluminum alkali mixed solution and complexing agent is controlled to control the drying and calcining conditions of the precipitate to form an aluminum fluoride clad layer. Stabilize spinel structure, inhibit lattice distortion, and improve cycle stability.

Benefits of technology

It effectively improves the cycle stability of lithium cobalt oxide positive electrode material, reduces cobalt dissolution and electrolyte corrosion, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114695862B_ABST
    Figure CN114695862B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material, comprising the following steps: (1) mixing a cobalt salt solution, an aluminum alkali mixed solution and a complexing agent to generate a precipitate; (2) performing solid-liquid separation on the material in step (1), washing the precipitate, and drying at a specific drying temperature to obtain a dried material, so that the cobalt hydroxide therein is decomposed into cobalt oxide, while the aluminum hydroxide is still stably present; (3) mixing the dried material obtained in step (2) with ammonium fluoroaluminate, calcining the mixture under a protective atmosphere, and then heat-insulating the mixture in an oxidizing gas to obtain a calcined material; (4) mixing the calcined material obtained in step (3) with a lithium-containing compound, and calcining the mixture under an oxygen atmosphere to obtain the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material. The positive electrode material prepared by the preparation method has good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium battery positive electrode materials, and in particular relates to a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, high operating voltage, low self-discharge, and environmental friendliness, and are widely used in portable electronic products and new energy vehicles. Among the commonly used lithium-ion positive electrode materials, lithium cobalt oxide is widely used in portable electronic products because of its simple production process, high gram capacity, stable cycle performance, and high compaction density. The theoretical capacity of lithium cobalt oxide is 274mAh / g, but the actual capacity is only about 140mAh / g. This is because the set charge and discharge potential is 2.5-4.2V, and only nearly half of the lithium ions can be released in this voltage range. In theory, increasing the charge cutoff voltage of lithium cobalt oxide will allow more lithium ions to be deintercalated, thereby obtaining a larger capacity. However, lithium cobalt oxide under high voltage causes the internal structure of the material to collapse due to the deep release of lithium ions, an irreversible phase change occurs, and cobalt is dissolved, resulting in a decrease in cycle performance.

[0003] At present, researchers mainly use bulk doping, surface coating, and bulk doping and surface coating to modify lithium cobalt oxide to improve the electrochemical performance of positive electrode materials. However, the modified lithium cobalt oxide positive electrode materials obtained by the existing modification methods still have the disadvantage of poor cycle stability. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material and a preparation method thereof, wherein the positive electrode material prepared by the preparation method has good cycle stability.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions:

[0006] A method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material comprises the following steps: (1) mixing a cobalt salt solution, an aluminum alkali mixed solution and a complexing agent to generate a precipitate; (2) subjecting the material in step (1) to solid-liquid separation, washing the precipitate, and drying it at a specific drying temperature to obtain a dried material, so that the cobalt hydroxide therein is decomposed into cobalt oxide, while the aluminum hydroxide is still stably present; (3) mixing the dried material obtained in step (2) with ammonium fluoroaluminate, calcining the mixture under a protective atmosphere, and then keeping the mixture warm in an oxidizing gas to obtain a calcined material; and (4) mixing the calcined material obtained in step (3) with a lithium-containing compound, and calcining the mixture under an oxygen atmosphere to obtain the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material.

[0007] Preferably, the mixing method in step (1) is to flow the cobalt salt solution, the aluminum base mixed solution and the complexing agent into a reaction container for reaction and monitor the D50 of the material in the reaction container in real time. When the D50 of the material in the reaction container reaches 4.0-8.0 μm, the feeding is stopped.

[0008] Preferably, during the co-current process of step (1), the stirring speed is controlled to be 200-500 r / min, the temperature is 70-80° C., the concentration of the complexing agent is 5-10 g / L, and the amount of cobalt added to the cobalt salt is maintained to be twice the amount of sodium added to the mixed solution.

[0009] Preferably, the drying temperature in step (2) is 160-170°C.

[0010] Preferably, the drying time in step (2) is 2-5 hours.

[0011] Preferably, in step (3), the dried material is mixed with ammonium fluoroaluminate in a cobalt to aluminum molar ratio of 10:(0.5-2).

[0012] Preferably, the calcination method in step (3) is to first heat the material under the protection of inert gas, with a heating rate of 0.5-10°C / min, a heating gradient from room temperature to 600-800°C and keep it warm for 1-2h, and then replace the oxidizing gas and keep it warm at 600-800°C for 4-6h.

[0013] Preferably, in step (4), the calcined material and the lithium-containing compound are mixed in a molar ratio of cobalt element to lithium element of 1:(1.0-1.2).

[0014] Preferably, the calcination in step (4) is carried out in an oxygen atmosphere at a temperature of 1050-1200° C. and a calcination time of 6-18 h.

[0015] Preferably, the lithium-containing compound in step (4) is at least one of lithium carbonate, lithium hydroxide, lithium nitrate and lithium oxalate.

[0016] Preferably, the complexing agent in step (1) is aqueous ammonia.

[0017] Preferably, the concentration of the ammonia solution in step (1) is 6.0-12.0 mol / L.

[0018] Preferably, the cobalt salt in the cobalt salt solution in step (1) is at least one of cobalt sulfate, cobalt nitrate and cobalt chloride.

[0019] Preferably, the concentration of the cobalt salt solution in step (1) is 1.0-2.0 mol / L.

[0020] Preferably, the aluminum alkali mixed solution in step (1) includes sodium tetrahydroxyaluminate and sodium hydroxide.

[0021] Preferably, in step (1), the concentration of sodium hydroxide in the aluminum alkali mixed solution is 1.0-4.0 mol / L, and the concentration of sodium tetrahydroxyaluminate is 0.05-0.4 mol / L.

[0022] Preferably, a method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material comprises the following steps:

[0023] (1) preparing a cobalt salt solution with a concentration of 1.0-2.0 mol / L, wherein the cobalt salt is at least one of cobalt sulfate, cobalt nitrate, and cobalt chloride;

[0024] (2) preparing an aluminum alkali mixed solution as a precipitant, wherein the concentration of sodium hydroxide in the aluminum alkali mixed solution is 1.0-4.0 mol / L, and the concentration of sodium tetrahydroxyaluminate is 0.05-0.4 mol / L;

[0025] (3) preparing ammonia water with a concentration of 6.0 mol / L-12.0 mol / L as a complexing agent;

[0026] (4) adding the cobalt salt solution prepared in step (1), the aluminum alkali mixed solution prepared in step (2), and the ammonia water prepared in step (3) to a reactor in parallel for reaction, controlling the stirring speed of the reactor to 200-500 r / min, the temperature in the reactor to 70-80° C., the ammonia concentration to 5-10 g / L, and maintaining the amount of cobalt added in the cobalt salt to be twice the amount of sodium added in the mixed solution;

[0027] (5) When the D50 of the material in the reactor is detected to reach 4.0-8.0 μm, stop feeding;

[0028] (6) separating the solid and liquid of the material in the kettle, washing the precipitate with pure water, and drying at 160-170° C. for 2-5 hours to obtain a dry material;

[0029] (7) mixing the dried material obtained in step (6) with ammonium fluoroaluminate in a cobalt-aluminum molar ratio of 10:(0.5-2), placing the mixture in a tubular furnace and introducing an inert gas to protect the mixture and heating the mixture. The heating rate is 0.5-10°C / min, and the temperature gradient is from room temperature to 600-800°C and kept for 1-2h. Then, the mixture is replaced with an oxidizing gas and kept at 600-800°C for 4-6h. After cooling, crushing, and sieving, a calcined material is obtained.

[0030] (8) According to the molar ratio of cobalt element to lithium element being 1:(1.0-1.2), the calcined material obtained in step (7) is mixed with at least one of lithium carbonate, lithium hydroxide, lithium nitrate and lithium oxalate, and then calcined in an air atmosphere at a calcination temperature of 1050-1200° C. for a calcination time of 6-18 h. After that, the mixture is crushed, sieved and iron removed to obtain a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material.

[0031] A fluorine-aluminum co-doped lithium cobalt oxide positive electrode material is prepared by the preparation method as described above.

[0032] A battery comprises the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material as described above.

[0033] The beneficial effects of the present invention are:

[0034] (1) The preparation method of the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material of the present invention is to mix sodium hydroxide and sodium tetrahydroxyaluminate, and then generate a coprecipitate of cobalt hydroxide and aluminum hydroxide with cobalt salt under the action of ammonia water, so that aluminum and cobalt are evenly mixed to form a eutectic; then the precipitate obtained after the coprecipitation is dried at 160-170°C, so that the cobalt hydroxide is decomposed into cobalt oxide, while the aluminum hydroxide is still stably present; then the dried material is evenly mixed with ammonium fluoroaluminate, and the mixture is first kept at 600-800°C in an inert atmosphere, and the following reactions occur: First, the ammonium fluoroaluminate reacts with the aluminum hydroxide in the dried material:

[0035] (NH4)3AlF6+Al(OH)3=2AlF3+3NH3↑+3H2O↑, forming a fluorine-aluminum co-doped lithium cobalt oxide precursor, and then, the ammonium fluoroaluminate self-decomposes: (NH4)3AlF6=AlF3+3NH4F↑, thereby forming an aluminum fluoride coating layer on the surface of the lithium cobalt oxide precursor, and keeping it at 600-800℃ in an oxidizing atmosphere, the following reaction occurs: 6CoO+O2=2Co3O4, and finally mixed with a lithium-containing compound and calcined at 1050-1200℃, the following reaction occurs: 4Co3O4+6Li2O+O2=12LiCoO2.

[0036] (2) The fluorine-aluminum co-doped lithium cobalt oxide positive electrode material of the present invention can improve the order of lithium cobalt oxide, stabilize the spinel structure, and inhibit lattice distortion through a specific preparation method. The use of AlF3 coating material can effectively alleviate capacity decay, effectively prevent corrosion from the electrolyte, and reduce the dissolution of cobalt, so that the obtained positive electrode material has excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a SEM image of the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with specific embodiments.

[0039] Embodiment 1:

[0040] A method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material comprises the following steps:

[0041] (1) preparing a cobalt sulfate solution with a concentration of 1.0 mol / L;

[0042] (2) preparing an aluminum alkali mixed solution as a precipitant, wherein the concentration of sodium hydroxide in the aluminum alkali mixed solution is 2.0 mol / L, and the concentration of sodium tetrahydroxyaluminate is 0.05 mol / L;

[0043] (3) preparing 6.0 mol / L ammonia water as a complexing agent;

[0044] (4) adding the cobalt sulfate solution prepared in step (1), the aluminum alkali mixed solution prepared in step (2), and the ammonia water prepared in step (3) to a reactor in parallel for reaction, controlling the stirring speed of the reactor to 200 r / min, the temperature in the reactor to 70° C., the ammonia concentration to 5 g / L, and maintaining the amount of cobalt added in the cobalt salt to be twice the amount of sodium added in the mixed solution;

[0045] (5) When the D50 of the material in the reactor is detected to reach 8.0 μm, the feeding is stopped;

[0046] (6) The material in the kettle is separated into solid and liquid, and the precipitate is washed with pure water and dried at 160° C. for 5 h to obtain a dry material;

[0047] (7) mixing the dried material obtained in step (6) with ammonium fluoroaluminate at a cobalt-aluminum molar ratio of 10:1, placing the mixture in a tubular furnace and introducing an inert gas to protect the mixture and heating the mixture. The heating rate is 0.5°C / min, and the temperature gradient is from room temperature to 600°C for 2 hours. Then, the mixture is replaced with an oxidizing gas and the mixture is kept at 600°C for 6 hours. After cooling, crushing, and sieving, a calcined material is obtained.

[0048] (8) According to the molar ratio of cobalt element to lithium element of 1:1, the calcined material obtained in step (7) is mixed with lithium carbonate and calcined in an air atmosphere at a calcination temperature of 1050° C. for 18 h. After that, the mixture is crushed, sieved and iron removed to obtain a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material.

[0049] A fluorine-aluminum co-doped lithium cobalt oxide positive electrode material is prepared by the above-mentioned preparation method.

[0050] The SEM image of the prepared fluorine-aluminum co-doped lithium cobalt oxide positive electrode material is as follows: Figure 1 shown.

[0051] Embodiment 2:

[0052] A method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material comprises the following steps:

[0053] (1) preparing a cobalt nitrate solution with a concentration of 1.5 mol / L;

[0054] (2) preparing an aluminum alkali mixed solution as a precipitant, wherein the concentration of sodium hydroxide in the aluminum alkali mixed solution is 1.0 mol / L, and the concentration of sodium tetrahydroxyaluminate is 0.05 mol / L;

[0055] (3) preparing 9.0 mol / L ammonia water as a complexing agent;

[0056] (4) adding the cobalt nitrate solution prepared in step (1), the aluminum alkali mixed solution prepared in step (2), and the ammonia water prepared in step (3) to a reactor in parallel for reaction, controlling the stirring speed of the reactor to 350 r / min, the temperature in the reactor to 75° C., the ammonia concentration to 8 g / L, and maintaining the amount of cobalt added in the cobalt salt to be twice the amount of sodium added in the mixed solution;

[0057] (5) When the D50 of the material in the reactor is detected to reach 6.0 μm, the feeding is stopped;

[0058] (6) The material in the kettle is separated into solid and liquid, and the precipitate is washed with pure water and dried at 165° C. for 3 h to obtain a dry material;

[0059] (7) mixing the dried material obtained in step (6) with ammonium fluoroaluminate at a cobalt-aluminum molar ratio of 10:1.3, placing the mixture in a tubular furnace and introducing an inert gas to protect the mixture and heating the mixture. The heating rate is 5°C / min, and the temperature gradient is from room temperature to 700°C and kept for 1.5 hours. Then, the mixture is replaced with an oxidizing gas and kept at 700°C for 5 hours. After cooling, crushing, and sieving, a calcined material is obtained.

[0060] (8) According to the molar ratio of cobalt element to lithium element of 1:1.2, the calcined material obtained in step (7) is mixed with lithium hydroxide and calcined in an air atmosphere at a calcination temperature of 1100° C. for 12 h. After that, the mixture is crushed, sieved and iron removed to obtain a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material.

[0061] A fluorine-aluminum co-doped lithium cobalt oxide positive electrode material is prepared by the above-mentioned preparation method.

[0062] Embodiment 3:

[0063] A method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material comprises the following steps:

[0064] (1) preparing a cobalt chloride solution with a concentration of 2.0 mol / L;

[0065] (2) preparing an aluminum alkali mixed solution as a precipitant, wherein the concentration of sodium hydroxide in the aluminum alkali mixed solution is 4.0 mol / L, and the concentration of sodium tetrahydroxyaluminate is 0.4 mol / L;

[0066] (3) preparing ammonia water with a concentration of 12.0 mol / L as a complexing agent;

[0067] (4) adding the cobalt chloride solution prepared in step (1), the aluminum alkali mixed solution prepared in step (2), and the ammonia water prepared in step (3) to a reactor in parallel for reaction, controlling the stirring speed of the reactor to 500 r / min, the temperature in the reactor to 80° C., the ammonia concentration to 10 g / L, and maintaining the amount of cobalt added in the cobalt salt to be twice the amount of sodium added in the mixed solution;

[0068] (5) When the D50 of the material in the reactor is detected to reach 4.0 μm, the feeding is stopped;

[0069] (6) The material in the kettle is separated into solid and liquid, and the precipitate is washed with pure water and dried at 170° C. for 2 h to obtain a dry material;

[0070] (7) mixing the dried material obtained in step (6) with ammonium fluoroaluminate at a cobalt-aluminum molar ratio of 10:2, placing the mixture in a tubular furnace and introducing an inert gas to provide protection for heating at a heating rate of 10°C / min, with a temperature gradient of heating from room temperature to 800°C for 1 hour, then replacing the mixture with an oxidizing gas and continuing to maintain the temperature at 800°C for 4 hours, and obtaining a calcined material after cooling, crushing, and sieving;

[0071] (8) According to the molar ratio of cobalt element to lithium element of 1:1.1, the calcined material obtained in step (7) is mixed with lithium nitrate and calcined in an air atmosphere at a calcination temperature of 1200° C. for 6 h. After that, the mixture is crushed, sieved and iron removed to obtain a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material.

[0072] A fluorine-aluminum co-doped lithium cobalt oxide positive electrode material is prepared by the above-mentioned preparation method.

[0073] Comparative Example 1:

[0074] A method for preparing a lithium cobalt oxide positive electrode material comprises the following steps:

[0075] (1) preparing a cobalt sulfate solution with a concentration of 1.0 mol / L;

[0076] (2) preparing a sodium hydroxide solution with a concentration of 2.0 mol / L;

[0077] (3) preparing 6.0 mol / L ammonia water as a complexing agent;

[0078] (4) adding the cobalt sulfate solution prepared in step (1), the sodium hydroxide solution prepared in step (2), and the ammonia water prepared in step (3) to a reactor in parallel for reaction, controlling the stirring speed of the reactor to 200 r / min, the temperature in the reactor to 70° C., the ammonia concentration to 5 g / L, and maintaining the amount of cobalt added in the cobalt salt to be twice the amount of sodium added in the mixed solution;

[0079] (5) When the D50 of the material in the reactor is detected to reach 8.0 μm, the feeding is stopped;

[0080] (6) The material in the kettle is separated into solid and liquid, and the precipitate is washed with pure water and dried at 160° C. for 5 h to obtain a dry material;

[0081] (7) placing the dried material obtained in step (6) in a tubular furnace and passing inert gas to heat the material, the heating rate is 0.5°C / min, the temperature gradient is from room temperature to 600°C and kept for 2 hours, then the oxidizing gas is passed and kept at 600°C for 6 hours, and after cooling, crushing and sieving, a calcined material is obtained;

[0082] (8) According to the molar ratio of cobalt element to lithium element being 1:1, the calcined material obtained in step (7) is mixed with lithium carbonate and calcined in an air atmosphere at a calcination temperature of 1050° C. for 18 h. The mixture is then crushed, sieved and iron removed to obtain a lithium cobalt oxide positive electrode material.

[0083] A lithium cobalt oxide positive electrode material is prepared by the above-mentioned preparation method.

[0084] Comparative Example 2:

[0085] A method for preparing a lithium cobalt oxide positive electrode material comprises the following steps:

[0086] (1) preparing a cobalt nitrate solution with a concentration of 1.5 mol / L;

[0087] (2) preparing a sodium hydroxide solution with a concentration of 1.0 mol / L;

[0088] (3) preparing 9.0 mol / L ammonia water as a complexing agent;

[0089] (4) adding the cobalt nitrate solution prepared in step (1), the sodium hydroxide solution prepared in step (2), and the ammonia water prepared in step (3) to a reactor in parallel for reaction, controlling the stirring speed of the reactor to 350 r / min, the temperature in the reactor to 75° C., the ammonia concentration to 8 g / L, and maintaining the amount of cobalt added in the cobalt salt to be twice the amount of sodium added in the mixed solution;

[0090] (5) When the D50 of the material in the reactor is detected to reach 6.0 μm, the feeding is stopped;

[0091] (6) The material in the kettle is separated into solid and liquid, and the precipitate is washed with pure water and dried at 165° C. for 3 h to obtain a dry material;

[0092] (7) placing the dried material obtained in step (6) in a tubular furnace and passing inert gas to increase the temperature, the heating rate is 5°C / min, the temperature gradient is from room temperature to 700°C and kept for 1.5 hours, then switching to oxidizing gas and continuing to keep at 700°C for 5 hours, cooling, crushing, and sieving to obtain a calcined material;

[0093] (8) According to the molar ratio of cobalt element to lithium element being 1:1.2, the calcined material obtained in step (7) is mixed with lithium hydroxide and then calcined in an air atmosphere at a calcination temperature of 1100° C. for 12 h. After that, the mixture is crushed, sieved, and iron removed to obtain a lithium cobalt oxide positive electrode material.

[0094] A lithium cobalt oxide positive electrode material is prepared by the above-mentioned preparation method.

[0095] Comparative Example 3:

[0096] A method for preparing a lithium cobalt oxide positive electrode material comprises the following steps:

[0097] (1) preparing a cobalt chloride solution with a concentration of 2.0 mol / L;

[0098] (2) preparing a sodium hydroxide solution with a concentration of 4.0 mol / L;

[0099] (3) preparing ammonia water with a concentration of 12.0 mol / L as a complexing agent;

[0100] (4) adding the cobalt chloride solution prepared in step (1), the sodium hydroxide solution prepared in step (2), and the ammonia water prepared in step (3) to a reactor in parallel for reaction, controlling the stirring speed of the reactor to be 500 r / min, the temperature in the reactor to be 80° C., the ammonia concentration to be 10 g / L, and maintaining the amount of cobalt added in the cobalt salt to be twice the amount of sodium added in the mixed solution;

[0101] (5) When the D50 of the material in the reactor is detected to reach 4.0 μm, the feeding is stopped;

[0102] (6) The material in the kettle is separated into solid and liquid, and the precipitate is washed with pure water and dried at 170° C. for 2 h to obtain a dry material;

[0103] (7) placing the dried material obtained in step (6) in a tubular furnace and passing inert gas to heat the material, the heating rate is 10°C / min, the temperature gradient is from room temperature to 800°C and kept for 1 hour, then the oxidizing gas is passed and kept at 800°C for 4 hours, and after cooling, crushing and sieving, a calcined material is obtained;

[0104] (8) According to the molar ratio of cobalt element to lithium element being 1:1.1, the calcined material obtained in step (7) is mixed with lithium nitrate and calcined in an air atmosphere at a calcination temperature of 1200° C. for 6 h. The mixture is then crushed, sieved and iron removed to obtain a lithium cobalt oxide positive electrode material.

[0105] A lithium cobalt oxide positive electrode material is prepared by the above-mentioned preparation method.

[0106] Test example

[0107] The lithium cobalt oxide positive electrode material prepared in Examples 1-3 and Comparative Examples 1-3 was used as the active material, acetylene black was used as the conductive agent, and PVDF was used as the binder. The active material, conductive agent, and binder were weighed in a ratio of 92:4:4, and a certain amount of organic solvent NMP was added. After stirring, they were coated on aluminum foil to make a positive electrode sheet. The negative electrode used a metal lithium sheet and a CR2430 button battery was made in a glove box filled with argon. The electrical performance test was carried out in a CT2001A blue electric test system. Test conditions: 3.0-4.48V, current density 1C=180mAh / g, test temperature 25±1°C, and the test results are shown in Table 1.

[0108] Table 1: Battery electrical performance test results

[0109]

[0110] It can be seen from Table 1 that the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material prepared by the preparation method of the present invention has good cycle stability, and its capacity retention rate after 600 cycles is 87% or above, which is much better than the capacity retention rate of the lithium cobalt oxide positive electrode material in the comparative example after 600 cycles.

[0111] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material, characterized in that: The following steps are involved: (1) mixing a cobalt salt solution, an aluminum alkali mixed solution and a complexing agent to generate a precipitate; (2) subjecting the material in step (1) to solid-liquid separation, washing the precipitate, and drying at a specific drying temperature to obtain a dry material, so that the cobalt hydroxide therein is decomposed into cobalt oxide, while the aluminum hydroxide still exists stably; (3) mixing the dried material obtained in step (2) with ammonium fluoroaluminate, calcining the mixture under a protective atmosphere, and then keeping the mixture warm in an oxidizing gas to obtain a calcined material; (4) mixing the calcined material obtained in step (3) with a lithium-containing compound and calcining the mixture in an oxygen atmosphere to obtain the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material; the drying temperature in step (2) is 160-170°C; the calcination method in step (3) is to first heat the material under the protection of an inert gas at a heating rate of 0.5-10°C / min, with a heating gradient from room temperature to 600-800°C and keep the temperature for 1-2h, and then replace the oxidizing gas and keep the temperature at 600-800°C for 4-6h.

2. The method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The mixing method in step (1) is to flow the cobalt salt solution, the aluminum base mixed solution and the complexing agent into a reaction container for reaction and monitor the D50 of the material in the reaction container in real time. When the D50 of the material in the reaction container reaches 4.0-8.0 μm, the feeding is stopped.

3. The method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material according to claim 1, characterized in that: In step (3), the dried material is mixed with ammonium fluoroaluminate in a cobalt to aluminum molar ratio of 10:(0.5-2).

4. The method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The calcination method in step (4) is calcination in an oxygen atmosphere, the calcination temperature is 1050-1200° C., and the calcination time is 6-18 hours.

5. The method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The complexing agent in step (1) is aqueous ammonia.

6. The method for preparing a fluorine-aluminum co-doped lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The aluminum alkali mixed solution in step (1) includes sodium tetrahydroxyaluminate and sodium hydroxide.

7. A fluorine-aluminum co-doped lithium cobalt oxide positive electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.

8. A battery, characterized in that: Including the fluorine-aluminum co-doped lithium cobalt oxide positive electrode material as described in claim 7.

Citation Information

Patent Citations

  • Lithium cobalt oxide material

    CN103228575A

  • Aluminum magnesium fluoride-coated lithium nickel cobalt manganese oxide positive electrode material and preparation method thereof

    CN106025212A

  • High-voltage and high-cycle type lithium cobalt oxide positive electrode material and preparation method therefor

    CN107591526A

  • Lithium ion battery positive electrode material and preparation method of precursor thereof

    CN107968201A

  • Negative and positive ion co-doped modified lithium ion battery positive material and preparation method thereof

    CN110323432A